How Useful is Pyrolysis‐GC/MS for the Assessment of Molecular Properties of Organic Matter in Archaeological Pottery Matrix? An Exploratory Case Study from North‐West Spain. (10th September 2013) - Kaal, J.; Lantes‐Suárez, O.; Martínez Cortizas, A.; Prieto, B.; Prieto Martínez, M. P.
Abstract : We applied pyrolysis‐GC/MS to archaeological potsherds from prehistoric settlements in north‐west Spain, some of which are conspicuously black or exhibit a black inner core from incomplete burn‐out. Virtually all pyrolysis products could be related to thermally modified material (partially polycondensed aromatics and short‐chain alkyl moieties) that most probably formed during firing (as opposed to cooking). Principal component analysis and supporting evidence (elemental composition, colour parameters and SEM microscopy) showed that the firing conditions (redox conditions and firing intensity) control pyrolysate composition. Laboratory experiments are required to fully understand the pyrolysis fingerprints and sample pre‐treatment might enhance the information obtained.